Measuring attentional bias in smokers during and after psychosocial stress induction with a Trier Social Stress Test in virtual reality via eye tracking - Schröder, Benedikt; Mühlberger, Andreas (Frontiers in Psychology, 2023)
Introduction Attentional bias (AB) is considered an important factor not only in the etiology of addiction, but also with respect to relapse. However, evidence for the predictive ability of AB for relapse is not robust. One reason for this might be fluctuations of AB due to stress. Therefore, the current study investigated whether AB was present during and after stress induction and whether AB was enhanced by stress induction. Methods A Virtual Reality (VR) adaptation of the Trier Social Stress Test (VR-TSST) was used to induce psychosocial stress in smokers (n = 34) and non-smokers (n = 37) followed by a novel free-viewing task in VR. Eye tracking data was recorded to examine gaze behavior to smoking-related and neutral stimuli presented in the VR-TSST and the free-viewing task. Results Stress ratings increased significantly from baseline to post VR-TSST in smokers and non-smokers. During the VR-TSST we observed, more frequent, longer, and earlier fixations on smoke-related compared with neutral stimuli without significant group differences. However, in the free-viewing task following the stress induction, a specific AB of smokers in terms of earlier and longer fixations on smoke stimuli was found. Conclusion Results indicate that AB is not a persistent trait in smokers, but is context dependent. It is suggested that emotional learning processes such as smoking in the context of relief after stress may contribute to changes of AB both in terms of increased initial attention and deeper stimulus processing. Additionally, the potential of the VR-TSST to induce psychosocial stress could be replicated.